Effect of Applied Methods and Materials on the Quality Control of Printed Coatings on Anodized Aluminium - Stamatina Theohari; Isidoros Iakovidis; Sanja Mahovic Poljacek (Research Highlights in Science and Technology Vol. 6, 2023)
This chapter presents studies on the processes, measurements and influencing parameters in the printing of anodized aluminium. Research results on treatment and anodization of commercially pure aluminium (AA1050) are presented, the properties of the printing inks and aluminium surface are examined, the printing parameters and measurements involved in characterization of applied coatings on the aluminium surface are determined. The investigation concerns the influence of mechanical pretreatment of pure aluminium by different types of grinding belts and other anodizing parameters (type of electrolyte, concentration, temperature, applied voltage or current density, etc.) on the printing quality. In addition, the role and parameters that determine the characteristic properties of the printed coatings are discussed. Two types of printing techniques were used, namely the ink-jet digital printing and the screen printing. The influence of different types of printing plates and printing inks, such as UV-curing inks or epoxy resin-based ones, as well as their interaction with aluminium surface in the printing process are investigated. Besides, the effect of the addition of nanoparticles, such as silicon dioxide (SiO2) and titanium dioxide (TiO2) to the prepared inks on the colorimetric properties and ageing stability of the coatings are discussed. The results presented in this study indicate that a suitable modification of the aluminium surface and the printing parameters results in an improvement of the stability, quality, and the outdoor resistance of the printed coatings. The present study demonstrates that optimum setting of all observed influential parameters is of high importance from an academic and a commercial point of view, especially when properties such as adhesion, weatherability, and resistance against chemicals are required in industrial applications, such as barcodes, labelling, panels, etc.